STUDY REGARDING THE IMPROVEMENT OF THE BOTTOM FRONT TAKEOVER IN VOLLEYBALL GAME (GIRLS - 14 - 16 YEARS) - Benedek Florian (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
Current efforts are of organizational nature, both by gaining a large number of investors but also through development programs designed to attract important financial funding for a proper activity. Development of volleyball, especially in children and youth and selecting talents at early ages, along with organizing centralized trainings and of some proper competition programs it is a major challenge of the present stage. For a combination game, when time one is used for a very long time, it is adopted for blockage the relationship 1 - 1, and the players from the second line advance a lot, zone 6 till 6 m, and the extreme players till 4 m, adverse attack combination sending the ball especially in the half field from the net.